INVESTIGATING STUDENTS’ SELF-EFFICACY IN SPEAKING THROUGH THE USE OF PROJECT-BASED LEARNING - Regina Putri Nernere; Markus Budiraharjo (Sanata Dharma University Yogyakarta, 2025)
This research explored the role of podcast-making project within project-based learning (PBL) framework in enhancing students' self-efficacy in speaking English. Fifty-three second-semester students from two intermediate listening and speaking classes at a private university in Yogyakarta's English Language Education Study Program (ELESP) participated. A sequential explanatory mixed-method approach was employed. To provide robust findings, the data were collected using questionnaires, interviews, and classroom observations to provide more comprehensive findings. Quantitative data were examined using paired sample t-tests, while thematic analysis was leveraged for the qualitative data. The findings disclosed a significant improvement in students' self-efficacy, as evidenced by an increase in mean scores and a decrease in variance, indicating greater consistency of confidence levels. In addition, the qualitative insights identified four major themes as the factors in enhancing students' self-efficacy: growth through personal challenge, modelling success as vicarious learning, collaborative environment, and emotional regulation and coping strategies. These findings suggested that integrating PBL, such as podcast-making, into language education can effectively foster students' self-efficacy and ability to communicate in real-world scenarios. Further implications are provided, suggesting that educators can adopt similar PBL activities to help learners overcome psychological barriers and develop a positive mindset toward speaking in English.